Development of Quizizz Game-Based Interactive Learning Media to Improve Learning Outcomes - Wahyuni, Wahyuni; Mariatun, Ika Lis; Sholeh, Yusrianto (research, training and philanthropy institution Natural Aceh, 2024)
In this digital era, it is very important to understand and use technology wisely to adapt to digital transformation. Technology affects the quality of education in these turbulent times. A game is an interesting learning medium with an interactive nature. Currently, educators can choose Quizizz as an interesting learning environment supporting the learning process. This study aims to provide teachers with interactive learning media interventions based on quizizz games in Economics class X SMA Darul Hadits, Sepulu District, Bangkalan Regency. This time, learning media development uses the research model (ADDIE). The research subjects included in the development of interactive learning media are validation tests by media validators, practitioner validators, and material validators, as well as tests aimed at students. Research data were obtained through observation techniques, questionnaires, and interviews with economics teachers and several class X SMA Darul Hadits regarding the learning process. The study results show that the teacher uses lecture and discussion methods using LKS and PowerPoint media in economics learning. So, with this, the researcher uses the Quizizz game application to support student learning enthusiasm so that later it will improve student learning outcomes. This study got a very good response from teachers and students.